Analyzing Digital Polarization on Hijab: A Dataset of Annotated YouTube Comments - Al Heraki, Heba; Zaghouani, Wajdi (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
This study presents an analysis of digital polarization on the topic of the Hijab by examining YouTube comments in Arabic. Employing a novel dataset of around 10K annotated comments, this research investigates the digital discourse using seven labels: Stance, Use of Sarcasm, Argumentation, Cordiality, Offensiveness, Hopefulness, and Apparent Gender of Commenters. The findings reveal significant insights into gender dynamics and the prevalence of specific rhetorical strategies within the debate. This study contributes to the broader field of polarization and argument mining, offering a unique lens on the intersection of digital culture and societal issues in the Arab context.